Thermomechanokinetics of viscoelastic deformation of smooth muscles in the rat gastrointestinal tract. II. Thermomechanokinetics of hysteresis of stomach and large intestine smooth muscles - O. V. Tsymbalyuk; S. O. Kosterin (Біологічні студії, 2012)
The thermomechanokinetical properties of smooth muscle to a certain extent determine the functional properties of the gastrointestinal tract. We has previously investigated the changes induced by temperature on the kinetics of elastic deformation of rats gastric smooth muscle. In the present study, the thermomechanokinetical properties of stress-induced deformation and relaxation (hysteresis curves) of smooth muscle strips of the stomach and the large intestine (colon and caecum) were analyzed. Proposed and tested mathematical phenomenological description of the hysteresis curves of muscles using quantitative parameters: force constants k1 and k2 (for the application and removal of the load, respectively); indexes P1/2,c (the load value, which causes the demimaximal strip deformation) and P1/2,r (the residual load, which is half the strip length recovery). An area of full cycle hysteresis is characterized hysteresis loop quantitatively, and serves as the energy characteristic of temporary irreversibility of the length return of deformed smooth muscle strips to the unladen condition. Using these quantitative parameters shows that the deformation of the stomach smooth muscle has a relatively low temperature sensitivity and physical sense is a passive process. Discusses possible mechanisms that cause thermoinduced mechanokinetical changes of hysteresis parameters in smooth muscles.